CONSUMER BEHAVIOR IN USING ONLINE SHOP ON NATIONAL CYBER AND CRYPTO AGENCY (NCCA) TRAINING CENTRE EMPLOYEE - Anggraini, Fariza; Mustaqim, Asrul (PEOPLE: International Journal of Social Sciences, 2020)
Information technology has changed the way of human life, especially in internet-based technology. The use of internet-based facilities lately is in great demand because it can make communication more effective and efficient. For example, the activities based on online nowadays are shopping through online shops. Database research shows that in 2018, the number of e-commerce transactions in Indonesia has reached around 144 trillion Rupiah. It means that Indonesian people tend to shop through online media. As many as 86% of Indonesian internet users shopping online through any device. Online shop is one of the innovations in shopping activities. One of the online buyers is the NCCA Training Centre employee. This research is a qualitative study using the Division of Innovation Theory. This research aims to see how the consumer behavior in using online shop among NCCA Training Centre Staff, from the perspective of diffusion innovation theory. This research is phenomenological. The population was all employees of the NCCA Training Centre. Samples were taken using a purposive sampling technique. The results showed that the diffusion of innovation of consumer behavior in using online shop among NCCA Training Centre employees was widespread, as evidenced by changes in how shopping at NCCA Training Centre employees who have now utilized online shop as one of the buying and selling media. However, even though the existence of an online shop can be well received, all informants are of the opinion that an offline shop is still needed